How to do Just About Everything - Editor: Rosen, Courtney and eHow (Glasgow HarperCollins, 2003)
This book has the answers to (just about) every question you might have. Whether you need to unclog a sink or wash your cat, you'll find clear, step-by-step instructions on how to do it. We collected 1,001 step-by-step solutions and then added special checklists, calendars, charts and tools that will help you get the job done quickly and easily.
Include Index
Keywords: Life skills -- Home economics -- Handbooks, manuals